Cervical proprioceptive impairment in patients with rheumatoid arthritis - DURUÖZ, MEHMET TUNCAY (SPRINGER HEIDELBERG, 2019)
Rheumatoid arthritis (RA) involving the cervical spine can lead to various neurologic defects and impairment of proprioception is just one of them. The aim of this study was the assessment of cervical proprioception and its relation with radiographic, clinical, and functional characteristics of patients with RA. One hundred and six rheumatoid arthritis patients who diagnosed according to the 2010 American College of Rheumatology/European League Against Rheumatism criteria and age, gender, educational status matched one hundred and six healthy volunteers were enrolled in this study. Cervical joint position error test (CJPET) was applied to healthy volunteers and RA patients for cervical proprioception assessment. Fatigue, depression, balance, quality of life and balance scales were administered to all patients. Cervical radiography was used to assess cervical subluxations. Regression analysis was used for grading the factors which had relations with cervical proprioception. Mean age of patients and healthy volunteers was 51 +/- 11.1 and 48.9 +/- 9.2, respectively. Scores of CJPET were statistically significantly higher in RA group than healthy volunteers (p = 0.001). CJPET scores were negatively correlated with Berg balance scale findings in right rotation, left rotation, flexion and extension (rho = - 0.421,- 0.473,- 0.448,- 0.515). There was weak or not significant correlation between the scores of CJPET and fatigue, depression, and quality of life scales. Scores of CJPET in patients with atlantoaxial subluxations (AAS) were statistically significantly higher than those without AAS (p < 0.05). Regression analysis results showed that the AAS was related to impaired cervical proprioception on right and left rotations. There was no correlation between CJPET scores and functional parameters. Cervical proprioception impaired in RA patients. This impairment was related to the existence of AAS and balance problems.
Keywords: Rheumatoid arthritis; Cervical proprioception; Proprioception; Atlantoaxial subluxation; Balance; CERVICOCEPHALIC KINESTHETIC SENSIBILITY; JOINT POSITION SENSE; NECK PAIN; CONSTRUCT-VALIDITY; SPINE INSTABILITY; TURKISH VERSION; RELIABILITY; BALANCE; INVOLVEMENT; DISABILITY